Identification of Three (Iso)flavonoid Glucosyltransferases From Pueraria lobata - Wang, Xin; Li, Changfu; Zhou, Zilin; Zhang, Yansheng (Frontiers in Plant Science, 2019)
(Iso)flavonoids are one of the largest groups of natural phenolic products conferring great value to the health of plants and humans. Pueraria lobata, a legume, has long been used in Chinese traditional medicine. (Iso)flavonoids mainly present as glycosyl-conjugates and accumulate in P. lobata roots. However, the molecular mechanism underlying the glycosylation processes in (iso)flavonoid biosynthesis are not fully understood. In the current study, three novel UDP-glucosyltransferases (PlUGT4, PlUGT15, and PlUGT57) were identified in P. lobata from RNA-seq data. Biochemical assays of these three recombinant PlUGTs showed all of them were able to glycosylate isoflavones (genistein and daidzein) at the 7-hydroxyl position in vitro. In comparison with the strict substrate specificity for PlUGT15 and PlUGT57, PlUGT4 displayed utilization of a broad range of sugar acceptors. Particularly, PlUGT15 exhibited a much higher catalytic efficiency toward isoflavones (genistein and daidzein) than any other identified 7-O-UGT from P. lobata. Moreover, the transcriptional expression patterns of these PlUGTs correlated with the accumulation of isoflavone glucosides in MeJA-treated P. lobata, suggesting their possible in vivo roles in the glycosylation.